(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Nowadays, the demand for learning foreign languages is increasing day by day because, in our interconnected world, the ability to speak multiple languages is more valuable than ever. We can say that learning foreign languages is a key skill for success in the future for several reasons. Learning foreign languages also helps us work closely with people from different countries and cultures around the world.